2010
DOI: 10.1007/s13213-010-0093-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and purification of O and H antigens from Salmonella Enteritidis as diagnostic tool

Abstract: Lipopolysaccharide (LPS) and flagellin are the major antigenic structures of Salmonella Enteritidis. Purified antigens are essential components for the diagnosis of and research on Salmonella Enteritidis. In this study, LPS were isolated and purified with modified hot phenol-water procedure in a yield of 6%. The flagellin isolation and purification were done by strong shaking with glass pearl beads with 3.9 mg/ml protein content. Purity was demonstrated on SDS-PAGE, ELISA and with colorimetric assay for both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Goat antimouse IgG, IgG1 and IgG2b peroxidase conjugate were from Southern Biotech. Assoc., Birmingham, AL, USA; lipopolysaccharide (LPS) was prepared from Salmonella Enteritidis 64K by hot water phenol extraction method (Nalbantsoy et al, 2010). Anti IL-2R␣ receptor (CD25) and CD69 antibodies were from R&D, USA; Histostain-Plus Bulk Kits was from Zymed, South San Francisco, USA; Mayer's hematoxylin was from Zymed Laboratories, USA; paraformaldehyde was from Sigma Chemical Co., St. Louis, USA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Goat antimouse IgG, IgG1 and IgG2b peroxidase conjugate were from Southern Biotech. Assoc., Birmingham, AL, USA; lipopolysaccharide (LPS) was prepared from Salmonella Enteritidis 64K by hot water phenol extraction method (Nalbantsoy et al, 2010). Anti IL-2R␣ receptor (CD25) and CD69 antibodies were from R&D, USA; Histostain-Plus Bulk Kits was from Zymed, South San Francisco, USA; Mayer's hematoxylin was from Zymed Laboratories, USA; paraformaldehyde was from Sigma Chemical Co., St. Louis, USA.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were injected with Salmonella Enteritidis derived LPS (Nalbantsoy et al, 2010) via single intraperitoneal injection (ip) of 12.5 g/mouse (100 l total injection volume) mixed with 60 g/mouse Ast VII or Mac B. The LPS dose was based on the results of two preliminary studies (data not shown).…”
Section: In Vivo Stimulationmentioning
confidence: 99%
“…Goat anti-mouse IgG, IgG1 and IgG2b peroxidase conjugate were from Southern Biotech. Assoc., Birmingham, AL, USA; lipopolysaccharide (LPS); prepared from Salmonella Enteritidis 64 K by hot water phenol extraction method (Nalbantsoy et al, 2010). All other chemicals were of AR grade.…”
Section: Methodsmentioning
confidence: 99%
“…The LPS isolation was done by modified Westphal and Jann procedure as lyophilised powder (Westphal & Jann, 1965;Nalbantsoy, Karaboz, & Deliloglu-Gurhan, 2010a). Estimation of the Kdo residues was performed by a modified thiobarbituric acid (TBA) assay as reported by Toman and Skultety (1996).…”
Section: Endotoxin Preparationmentioning
confidence: 99%